Bacaan Unik Dalam Al-Qur’an Perspektif I’jaz Lughawi - S. Inaku, Miskat; Rawandhi N. Hula, Ibnu (Assuthur: Jurnal Pendidikan Bahasa Arab, 2022)
This research aims to reveal the variations of readings in the Qur'an, namely some readings that are considered unique to be subsequently studied using the date of ash-syatibiyyah, the type of research used is literature research, so that the results of this research are: (1) The technique, Among the unique readings in the Qur'an that have undergone changes in reading is the reading of Imam Qiraat seven using the date technique asy-Syatibiyyah where each rule is accompanied by a syatibiyyah stanza. (2) Qiraat aspect, In this case the pronunciation of the Qur'an focuses on changing the reading such as the recitation of fath, imalah, and taqlil according to the recitation of Imam qiraat seven. (3) Aspect of Tarikhiyah ̧ The Arab nation has diversity in various lahjah (dialects) between one tribe and another. Both in terms of sound, intonation and letters. And the cause of the still ongoing difference in qiraat is none other than because the readings that still exist in the memory of qiraat and hafizh experts do not seem to be forever abandoned by them even though in front of them there is already an Ottoman mushaf which is the standard for all Muslims in reading the Qur'an. (4) The aspect of i'jaz lughawi, the recitation of imalah in the word majreeha  has wisdom and guidance so that the reader of the Qur'an when reading imalah can feel the tilt of the Ark of the Prophet Noah while sailing between the great waves based on Surah Hud:41.